PLANEJAMENTO TERRITORIAL: SUAS IMPLICAÇÕES PARA A PROMOÇÃO DA SAÚDE E DA JUSTIÇA AMBIENTAL - Pereira, Rafaela Rodrigues (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2009)
The longstanding territorial urban planning is the focus of shares of public power. The Status of Cities, which regulates the articles of the constitution which deal with the federal urban policy, has been considered by some scholars, one of the biggest advances in terms of legal management and urban planning in Brazil. In its section I, The Status of cities poses as one of the instruments of territorial urban planning at the municipal level, the plan director. This, in turn, in legal terms, is to be a tool dedicated to the exclusive management of urban areas, in spite of its radius of action, in some municipalities, cover urban and non-urban - rural areas. At this point, is the question: Since this management tool incorporates the demands and environmental conflicts inherent in such private areas, not urban, but intrinsically inserted in the network configuration urban and who see suffering multiple and different pressures of the media, of the urban logic? Therefore, in this article, for it will work up to the subject, from a broader discussion about environmental injustice and inequality socio-spatial, focusing, gradually, on the issue of spatial inequalities within municipality in municipalities where verifies the existence of environmental conflicts from the rural-urban interface. In this context, the master plan is a management tool that has the potential to mediate the conflict mentioned.